2018
DOI: 10.1093/jn/nxx027
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry Supplementation Influences the Gut Microbiota, Inflammation, and Insulin Resistance in High-Fat-Diet–Fed Rats

Abstract: In HF-diet-fed male rats, blueberry supplementation led to compositional changes in the gut microbiota associated with improvements in systemic inflammation and insulin signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
202
3
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(217 citation statements)
references
References 67 publications
9
202
3
3
Order By: Relevance
“…On the other hand, anthocyanins are capable of modulating the growth of special intestinal bacteria [24] and increasing microbial abundances [64]. Anthocyanins have been reported to increase the relative abundance of beneficial bacteria such as Bifidobacterium and Akkermansia, which are believed to be closely related to anti-inflammatory effects [24,65].…”
Section: Crosstalk Between Gut Microbiota and C3gandc3g-msmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, anthocyanins are capable of modulating the growth of special intestinal bacteria [24] and increasing microbial abundances [64]. Anthocyanins have been reported to increase the relative abundance of beneficial bacteria such as Bifidobacterium and Akkermansia, which are believed to be closely related to anti-inflammatory effects [24,65].…”
Section: Crosstalk Between Gut Microbiota and C3gandc3g-msmentioning
confidence: 99%
“…In addition to the influence on gut microbiota, the inhibitory effect of anthocyanins on epithelial inflammation is another important factor that acts against intestinal injury [64,76]. Ferrari et al have demonstrated that the main protective effect of C3G in chronic gut inflammatory diseases is derived from the selective inhibition of the NF-κB pathway in epithelial cells [76].…”
Section: Anti-inflammatorymentioning
confidence: 99%
“…Eight‐week supplementation of wild blueberry powder to obese Zucker rats reduced plasma levels of pro‐inflammatory markers, including tumor necrosis factor alpha (TNFα), interleukin‐6 and C‐reactive protein, that are known to promote endothelial monocyte adhesion . Blueberry consumption reduced serum TNFα and Interleukin‐6, and downregulated aortic TNFα expression in apolipoprotein E‐deficient mice and reduced high‐fat diet–induced chronic inflammation in rats . In these animal studies, the anti‐inflammatory effects were tentatively attributed to the presence of blueberry polyphenols such as anthocyanins and/or proanthocyanidins .…”
Section: Introductionmentioning
confidence: 97%
“…With the critical roles of the gut microbiota and its communication with the gut-brain axis in the pathogenesis of obesity and metabolic complications, modulation of the gut microbiota composition has been an attractive target to prevent and/or treat those abnormalities [22][23][24]. In particular, since the diet has been associated with critical alterations in the gut microbiota [25], the use of non-invasive dietary approaches such as prebiotics in the presence of HF challenge have been reported to increase beneficial bacteria abundance, decrease local (gut, adipose) and systemic inflammation and preserve vagally-mediated satiety signaling, which is all associated with suppression of adiposity and weight gain [23,26,27]. the underlying mechanisms responsible for these metabolic benefits are not only via modulation of the host gut microbiota composition but also via associated changes in the production of microbial metabolites.…”
Section: Introductionmentioning
confidence: 99%